2022
DOI: 10.3390/ma15072363
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Mechanical Properties of Fly Ash-Based Geopolymer Composites with PVA Fiber and Powder

Abstract: In this work, polyvinyl alcohol (PVA) fiber and powder were added to geopolymer composites to toughen fly ash-based geopolymer, and their different toughening mechanisms were revealed. Firstly, different contents of active granulated blast furnace slag (GBFS) were added to the geopolymer to improve the reactivity of the GBFS/fly ash-based geopolymer, and the best ratio of GBFS and fly ash was determined through experiments testing the mechanical properties. Different contents of PVA powders and fibers were uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…The weight loss for the fly ash geopolymer specimens that were incorporated in kaolin occurred at approximately 100 • C. When the temperature increased, while the fly ash-based geopolymer-incorporated kaolin showed a complex curve type, a relatively sharp dip in weight was monitored. The examination of both specimens made it obvious that the ideal temperature for curing might range from 80 • C to 100 • C. Cai et al [414] explained that the earliest method of quality deterioration was dehydration. The authors toughened fly ash-based geopolymer by using polyvinyl alcohol (PVA) fibre and powder geopolymer composites.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…The weight loss for the fly ash geopolymer specimens that were incorporated in kaolin occurred at approximately 100 • C. When the temperature increased, while the fly ash-based geopolymer-incorporated kaolin showed a complex curve type, a relatively sharp dip in weight was monitored. The examination of both specimens made it obvious that the ideal temperature for curing might range from 80 • C to 100 • C. Cai et al [414] explained that the earliest method of quality deterioration was dehydration. The authors toughened fly ash-based geopolymer by using polyvinyl alcohol (PVA) fibre and powder geopolymer composites.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…Natali et al [26] systematically studied the effects of carbon fiber, glass fiber, PVA fiber, and polyvinyl chloride (PVC) fiber on improving the toughness of geopolymers. Cai et al [27] revealed the toughening mechanisms, mechanical properties, freeze-thaw cycle resistance, and thermal decomposition properties of PVA fiber-reinforced geopolymer.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that fiber incorporation increased the compressive strength and elastic modulus of ECC and EGC, with PVA fibers performing significantly better than PET and PP fibers. Cai et al [23] varied the form of PVA fiber incorporation and the amount of incorporation to investigate the properties of the geopolymer. The results showed that the incorporation of PVA powder did not enhance the mechanical properties of the geopolymer, and no reaction occurred.…”
Section: Introductionmentioning
confidence: 99%